2020
DOI: 10.1159/000503724
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Mechanism of TRPC1, 3, and 6 on the Proliferation, Migration, and Lumen Formation of Retinal Vascular Endothelial Cells Induced by High Glucose

Abstract: Objective: Transient receptor potential canonical (TRPC) channels are involved in neovascularization repairing after vascular injury in many tissues. However, whether TRPCs play a regulatory role in the development of diabetic retinopathy (DR) has rarely been reported. In the present study, we selected TRPC1, 3, and 6 to determine their roles and mechanism in human retina vascular endothelial cells (HREC) under high glucose (HG) conditions. Methods: HRECs were cultured in vitro under HG, hyper osmosis, and nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Studies have shown that MALAT1 can regulate gene variable shearing by regulating phosphorylation of SR shearing factor [15]. Hai-Bo et al [5] found that MALAT1 silence significantly inhibited the proliferation and migration of human osteosarcoma cells and speculated that PI3K/AKT signal played a certain role in promoting it. Xiao et al [16] think that the recurrence after operation is closely related to the size of intracranial aneurysms, and the recurrence rates of aneurysms smaller than 10 mm and larger than 10 mm are 16.9% and 36.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that MALAT1 can regulate gene variable shearing by regulating phosphorylation of SR shearing factor [15]. Hai-Bo et al [5] found that MALAT1 silence significantly inhibited the proliferation and migration of human osteosarcoma cells and speculated that PI3K/AKT signal played a certain role in promoting it. Xiao et al [16] think that the recurrence after operation is closely related to the size of intracranial aneurysms, and the recurrence rates of aneurysms smaller than 10 mm and larger than 10 mm are 16.9% and 36.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Shosha et al [4] specifically deleted cardiac ATG5, which led to the early expression of aging phenotype, and began to die from six months of mice. Compared with wild-type mice, mice without ATG5 showed myocardial hypertrophy, fibrosis, and abnormal mitochondria in old age [5]. Fittipaldi et al [6] found that miR-30a can negatively regulate autophagy in tumor cells.…”
Section: Related Workmentioning
confidence: 99%
“…Primers were designed in accordance with a previous study. 20 Glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) was used as internal references; meanwhile, TRPC1 expression was calculated using the 2 –ΔΔCt method.…”
Section: Methodsmentioning
confidence: 99%
“…found that TRPC3 could inhibit cardiac fibrosis in type 1 diabetes ( 19 ); Lang et al. found that TRPC3 could inhibit high glucose-induced endothelial cell proliferation and migration ( 20 ). ; liu et al.…”
Section: Discussionmentioning
confidence: 99%